Enhanced and switchable silicon-vacancy photoluminescence in air-annealed nanocrystalline diamond films. (January 2020) - Yang, Bing; Yu, Biao; Li, Haining; Huang, Nan; Liu, Lusheng; Jiang, Xin
Abstract: Silicon vacancy (SiV) centers in CVD-deposited nanodiamond particles or films always exhibit a photoluminescent (PL)-quenching behavior. Herein, in order to overcome this issue, air annealing of nanocrystalline diamond (NCD) films with uniform doping of Si atoms is employed to improve the PL emission efficiency of SiV centers. Without severe mass loss in diamond, SiV centers exhibit an increased PL emission intensity at 738 nm with an increased annealing temperature and time. In comparison to the untreated film, the maximum PL enhancement reaches about 200 and 1473 folds when the NCD films are annealed at 600 °C for 60 min and 700 °C for 20 min, respectively. Such giant increase in SiV PL emission is mainly attributed to the transition of diamond surface from hydrogen to oxygen termination together with the optimized crystalline quality of the annealed films, as confirmed by the HRTEM, Raman and XPS measurements. A schematic model based on the theory of surface band bending is proposed to elucidate the mechanism of the SiV PL enhancement in oxygen-terminated NCD films: a near-surface light trap layer formed in hydrogen-terminated NCD is converted during the oxidation process, leading to the additional collection of SiV PL emission from the inner layer. Graphical abstract: Description: The PL intensity of SiV centers in NCD films is enhanced by 1473 folds in the oxidized condition compared with that of H-terminated films Image 1